2018
DOI: 10.1097/iae.0000000000001828
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Microvasculature and Visual Acuity After Intravitreal Aflibercept in Eyes With Central Retinal Vein Occlusion

Abstract: Patients with better retinal perfusion and less retinal ischemia are associated with better visual outcomes after aflibercept in eyes with central retinal vein occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
4
17
0
Order By: Relevance
“…Agreed with previous study, our result suggested DCP was more vulnerable to ischemic changes and BRVO may cause a more extensive vascular alteration. Recent studies found enlarged FAZ in superficial and deep retinal layer in BRVO eyes [23,25,26], which was negatively correlated with visual acuity [23,25,27]. In our study, FAZ size and perimeter were larger in BRVO eyes compared with fellow eyes, which agreed with previous reports.…”
Section: Discussionsupporting
confidence: 92%
“…Agreed with previous study, our result suggested DCP was more vulnerable to ischemic changes and BRVO may cause a more extensive vascular alteration. Recent studies found enlarged FAZ in superficial and deep retinal layer in BRVO eyes [23,25,26], which was negatively correlated with visual acuity [23,25,27]. In our study, FAZ size and perimeter were larger in BRVO eyes compared with fellow eyes, which agreed with previous reports.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies found enlarged FAZ in superficial and deep retinal layer in BRVO eyes [23,25,26], which was negatively correlated with visual acuity [23,25,27]. In our study, FAZ size and perimeter were larger in BRVO eyes compared with fellow eyes, which agreed with previous reports.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies found enlarged FAZ in superficial and deep retinal layer in BRVO eyes [23,25,26], which was negatively correlated with visual acuity [23,25,27]. In our study, FAZ area and perimeter were larger in BRVO eyes compared with fellow eyes, which agreed with previous reports.…”
Section: Macular Vessel Densitysupporting
confidence: 92%